Parâmetros clínicos, laboratoriais e pulmonares de cães naturalmente infectados com parvovírus (PVC-2) em sepse grave e tratados seriadamente com solução salina hipertônica a 7,5% - Breno Curty Barbosa (2020)
Canine parvovirus is responsible for high mortality rates in the small animal clinic for triggering septic conditions. The most relevant clinical findings of this disease include the intense leukopenia associated with sepsis and its consequences, with emphasis on severe sepsis with dysfunctions in vital organs. However, in patients with parvovirus, the acute respiratory distress syndrome (ARDS), responsible for high mortality rates due to intense hypoxemia, is poorly investigated, as well as it has few treatment alternatives. Thus, strategies that positively impact these patients, such as elevating WBC and the control of lung injuries, as well as the use of early biomarkers, are currently of great relevance in veterinary clinic. The objective of this study was to evaluate the behavior of 7.5% SSH applied serially in dogs naturally infected with canine parvovirus type 2 (PVC-2), verifying the presence of ARDS in leukopenic dogs, the serum values of biomarkers and the possible effects on the reversal of leukopenia and length of stay. For this purpose, the results of physical, radiographic and laboratory tests were evaluated, the latter consisting of blood count, serum biochemical profile, blood gas analysis, procalcitonin and serum amyloid A, of animals naturally infected by PVC-2, in severe sepsis and randomly distributed in a group control treated with Lactate Ringer (CON) and a group treated with 7.5% hypertonic saline solution (SSH). It is concluded that the use of 7.5% SSH has positive effects in the treatment of canine parvovirus.